Resilience in rail engineering work - Ferreira, Pedro (2013)
This paper discusses an ongoing project that aims at improving the potential for resilience of a system responsible for the planning of rail engineering work delivery. This is being addressed by means of a methodology based on the observation and analysis of “real” planning activities, using resilience engineering concepts as a background. Interviews with planners have been carried out to provide an overview of the planning process and steer more in-depth investigation. Analysis of historic information and observation of planners’ main activities is underway. Given the nature of the process under study, information flows and communication issues have been given particular attention throughout the data collection and analysis stages. Initial data confirms that the planning process is greatly reliant on the capability of people using their knowledge and skills to communicate in a dynamic informational environment. Evidence was found of communication breakdowns at the boundaries of different planning levels and teams. The fact that the process is divided amongst several different areas of the organisation, often with different goals and needs, creates potential sources of conflict and tension.